2019
DOI: 10.1021/acsami.9b03195
|View full text |Cite
|
Sign up to set email alerts
|

8% Efficiency Cu2ZnSn(S,Se)4 (CZTSSe) Thin Film Solar Cells on Flexible and Lightweight Molybdenum Foil Substrates

Abstract: The use of flexible and highly conducting molybdenum (Mo) foil as a substrate offers several advantages such as a high thermal stability, smooth surface, and chemical inertness for the fabrication of high-efficiency thin film solar cells (TFSCs) by lowering the manufacturing costs. Here, we report a record preliminary efficiency of ∼8% for sputtered-grown Cu 2 ZnSn(S,Se) 4 (CZTSSe) TFSCs on flexible and lightweight Mo foils. Careful studies were focused on identifying the role of preparative parameters such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…When the E g of the absorption layer is small, the spectral response range of the device is larger, which leads to a larger current density. The Jsc obtained in this work is comparable to that reported in other literatures about the CZTSSe film solar cells with high efficiency [ 39 , 40 ]. This also further improves that doping a small amount of Mn is an appropriate way to improve the efficiency of CZTSSe solar cells.…”
Section: Resultssupporting
confidence: 89%
“…When the E g of the absorption layer is small, the spectral response range of the device is larger, which leads to a larger current density. The Jsc obtained in this work is comparable to that reported in other literatures about the CZTSSe film solar cells with high efficiency [ 39 , 40 ]. This also further improves that doping a small amount of Mn is an appropriate way to improve the efficiency of CZTSSe solar cells.…”
Section: Resultssupporting
confidence: 89%
“…[5][6][7][8][9][10][11][12][13][14] In addition, alkali doping is essential when flexible substrates are employed in place of the more commonly used rigid soda-lime glass (SLG) due to Na and K diffusion effects. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] López-Marino et al [15] compared alkali doping methods such as MoNa back contact, NaF and KF layers with a 6.1% PCE of flexible Cu 2 ZnSnSe 4 solar cells. They achieved the highest efficiency when using MoNa back contact, but the contents of alkali elements of each doping method were not strictly controlled.…”
Section: Introductionmentioning
confidence: 99%
“…If the MoNa layer directly touches the substrate or the absorbing layer, it leads to bad adhesion or interface recombination, so they solved it by adding the Mo layer on both sides of the MoNa layer. Interestingly, Jo et al [16] obtained 8.0% PCE for flexible CZTSSe solar cells due to high short circuit current (J SC ) and open-circuit voltage (V OC ) without alkali doping, but a fill factor (FF) was low. Yang et al [20] reported 10.34% PCE for flexible CZTSSe solar cells, which is considered the record efficiency, and its enlarging methods using multilayered precursor structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations